An Embodied Approach to Perception: By What Units Are Visual Perceptions Scaled?. (July 2013) - Proffitt, Dennis R.
When humans perceive the environment, angular units of visual information must be transformed into units appropriate for the specification of such parameters of surface layout as extent, size, and orientation. Our embodied approach to perception proposes that these scaling units derive from the body. For example, hand size is relevant for scaling the size of a strawberry, whereas an extent across a meadow is scaled by the amount of walking required to traverse it. In his article, Firestone (2013, this issue) argued that our approach is wrong; in fact, he argued that it must be wrong. This reply to Firestone's critique is organized into three parts, which address the following questions: (a) What is the fundamental question motivating our approach? (b) How does our approach answer this question? (c) How can we address Firestone's arguments against our approach? A point-by-point critique of Firestone's arguments is presented. Three conclusions are drawn: (a) Most of Firestone's arguments reflect a misunderstanding of our approach, (b) none of his arguments are the fatal flaws in our approach that he believes them to be, and (c) there are good reasons to believe that perception—just like any other biological function—is a phenotypic expression.